Development and preliminary evaluation of the Comprehensive Health Self-Assessment Questionnaire (CHSAQ) for individuals in the Chinese People Liberation Army - Tao Wang; Han Tang; Xinrui Li; Lin Wu; Ning Li; Wei Zhang; Qiongjie Shao; Min Cai; Lei Shang (BMC, 2024)
Abstract Objective There is currently no widely accepted multidimensional health assessment questionnaire for individuals in the Chinese People Liberation Army (PLA). This study developed a multidimensional health survey questionnaire (Comprehensive Health Self-Assessment Questionnaire, CHSAQ) suitable for personnel in the PLA and conducted a preliminary examination of its reliability, validity, and discriminative ability. Methods After 183 items from 32 dimensions were selected to form the initial version of the CHSAQ, three groups of soldiers were selected from May 2022 to April 2023 and completed three survey rounds (with 183, 131, and 55 valid items). The items were screened based on classic test theory. After screening, the final questionnaire entries were formed, the structure of the questionnaire was explored through exploratory factor analysis and confirmatory factor analysis, and its reliability, structural validity, and discriminative ability were evaluated. Results The final questionnaire consisted of 8 dimensions and 55 items on job satisfaction, anxiety and depression, daily activities, physical function, the otolaryngology system, the integumentary system, sleep disorders, and the visual system. The total cumulative variance contribution rate was 64.648% according to exploratory factor analysis. According to the confirmatory factor analysis, the normed fit index (NFI) was 0.880, and the comparison fit index (CFI) was 0.893 (close to 0.90). The Cronbach's α coefficient of the total questionnaire was 0.970, the split half reliability coefficient was 0.937, and the retest reliability coefficient was 0.902. The results are presented as different pairwise comparisons. Conclusion Our study developed a self-report questionnaire for evaluating the comprehensive health status of personnel in the PLA in accordance with the standard procedure for questionnaire development. Our findings also showed that the CHSAQ for individuals in the PLA has good reliability and structural validity.